Теорія зацікавлених сторін: основні положення та сфери дослідження - Краснокутська, Наталія Станіславівна; Ришкова, Яна Сергіївна (Харківський державний університет харчування та торгівлі, 2014)
Розглянуто сутність і понятійний апарат теорії зацікавлених сторін (стейкхолдерів); обґрунтовано її основні положення з урахуванням сучасних підходів до розуміння сенсу існування підприємства; узагальнено підходи до класифікації ключових стейкхолдерів і визначено зміст основних областей дослідження теорії зацікавлених сторін.

Today, the focus of the institutional theory of firm is shifted towards the stakeholder theory – an alternative to the neoclassical theory of firm that based on meeting the interests of the various participants in business activity. This direction, on the one hand, has considerable theoretical and applied significance, and on the other hand, is characterized by a certain incompleteness and inconsistencies. The paper considers the essence and the main concepts of the stakeholder theory, substantiates its key tenets according to the current approaches to understanding the enterprise’s raison d'etre; determines that all groups or individuals that influence on company business activities are its stakeholders whose interests should be considered by management; summarizes the approaches to the classification of the key stakeholders and determines the content of the main research areas of stakeholder theory (who are stakeholders, what are their interests and what are the ways they can realize these interests).
Stakeholder theory: basic provisions and field studies
Keywords: стейкхолдер; підприємство; інтреси; вплив; stakeholder; theory; firm interest; influence